Cervicovaginal Microbiome Factors in Clearance of Human Papillomavirus Infection - Dai, Wenkui; Du, Hui; Li, Shuaicheng; Wu, Ruifang (Frontiers in Oncology, 2021)
Persistent high-risk human papillomavirus (hrHPV) infection is the highest risk of cervical cancer which is the fourth most common cancer in women worldwide. A growing body of literature demonstrate the role of cervicovaginal microbiome (CVM) in hrHPV susceptibility and clearance, suggesting the promise of CVM-targeted interventions in protecting against or eliminating HPV infection. Nevertheless, the CVM-HPV-host interactions are largely unknown. In this review, we summarize imbalanced CVM in HPV-positive women, with or without cervical diseases, and the progress of exploring CVM resources in HPV clearance. In addition, microbe- and host-microbe interactions in HPV infection and elimination are reviewed to understand the role of CVM in remission of HPV infection. Lastly, the feasibility of CVM-modulated and -derived products in promoting HPV clearance is discussed. Information in this article will provide valuable reference for researchers interested in cervical cancer prevention and therapy.